Adverse neonatal outcomes according to degrees of pre-gestational obesity in a public hospital in southern Peru, 2010 to 2019 - Ticona Rendón, Manuel (2022)
Introduction: Maternal obesity, a growing global public health problem, is related to neonatal morbidity and mortality. The objective was to determine adverse neonatal outcomes according to degrees of pregestational obesity. Material and method: Analytical study, retrospective cohort, in pregnant women with a single pregnancy, delivery attended at the Hipolito Unanue hospital in Tacna, Peru, during 2010 to 2019, with live newborns, the cases were 5935 mothers with pre-pregnancy body mass index from 30 Kg/m2 to more, grouped in grade I (BMI 30-34.9 Kg/m2), II (BMI 35-39.9 Kg/m2) and III (BMI>40 Kg/m2), the control mothers with a BMI of 18-24.9 Kg/m2. Pregnant women with diabetes mellitus, preeclampsia, eclampsia and congenital anomalies were excluded. Crude Relative Risk (RR) was used, adjusted for maternal age, schooling and parity, with a 95% confidence interval. Results: The frequency of pre-pregnancy obesity was 14.3% grade I, 3.8% grade II and 1% grade III. The associated neonatal outcomes were: birth weight >4000 grams, for grade I obesity (RRa: 1.9; 95% CI: 1.7-2.0), grade II (RRa: 2.0; 95% CI: 1.8-2.3) and grade III (RRa: 2.1; CI95%: 1.7-2.5); large for gestational age for grade I (RRa: 1.6; 95% CI: 1.4-1.7), grade II (RRa: 1.7; 95% CI: 1.6-1.9) and grade III (RRa: 1.8; CI95%: 1.4-2.1). Conclusions: There is an increased risk of fetal macrosomia and large for gestational age with a higher degree of maternal pregestational obesity